Efficacy of intravenous Tramadol in prevention of catheter-related bladder discomfort in upper urinary tract surgery - Manandhar, Sujita; Manandhar, Kishor (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Catheter-related bladder discomfort (CRBD) is common in patients with urinary catheterization. Centrally acting intravenous opioid like Tramadol inhibits detrusor activity and incidence of CRBD. Present study aims to analyze efficacy of intravenous (IV) Tramadol in prevention of CRBD in patients undergoing upper urinary tract surgery. Methods: Adult patients undergoing elective open upper urinary tract surgeries at Bir Hospital, National Academy of Medical Sciences (NAMS), Nepal, over a period of six months, requiring urinary catheterization were randomly divided into Control (C) and Tramadol (T) groups. After general anesthesia, patients in T-group received IV Tramadol 1.0 mg/kg and C-group received normal saline 30 minutes before extubation. In post-operative ward, CRBD was graded as mild, moderate or severe at 0, 1, 2 and 6 hours. Post-operative Ramsay sedation score and nausea vomiting were compared in two groups. Results: There were total 70 patients, 35 in each of groups-T and C. Incidence of CRBD in T-group was significantly low compared to the C-group at all points of evaluation (p<0.05). Postoperative sedation score, analgesic requirement and nausea vomiting were not significantly different in two groups. Conclusions: Intravenous Tramadol administered before extubation in upper urinary tract surgery reduces the incidence of CRBD.